Legal Review of the Appointment of Specific Positions to Family Members and Close Associates in Government by Regional Heads in Relation to Criminal Acts of Corruption - Laritmas, Selfianus (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The granting of certain positions to family members by regional heads in connection with criminal acts of corruption in government has become highly controversial because it has implications for social welfare and public perceptions of government integrity. In theory, regional heads granting certain positions to family members in connection with criminal acts of corruption or nepotism will exacerbate existing social stratification because government positions or benefits are given based on family ties or close relationships rather than merit. This has an impact on inequality of opportunity and distribution of resources, as seen in several cases such as the former Governor of Banten, Ratu Atut Chosiyah, and the former Governor of North Maluku, Abdul Gani Kasuba, who are suspected of using their political power to appoint family members to important positions in the government, which has triggered negative perceptions among the government and the people and has an impact on indications of corruption. The regulation on nepotism in Law No. 28 of 1999 prohibits appointments based on family ties, prioritizes meritocracy, and imposes sanctions for violations. The research method used in this study is a normative legal approach, which involves analyzing existing literature. The research conducted by the author was aimed at using several approaches, including the statute approach, conceptual approach, case approach, and historical approach.